Experimental study on compressive buckling behavior of J-stiffened composite panels. (September 2019) - Liu, Da; Bai, Ruixiang; Wang, Ru; Lei, Zhenkun; Yan, Cheng
Highlights: Fringe projection profilometry was applied to measure the buckling morphology of J-stiffened composite panel under compression. The full-field deflections showed that concaves and convexes interval distributed on the skin. The failure load and buckling modes were verified by FEM prediction. Abstract: Fringe projection profilometry was used to study compressive buckling behavior of composite panels stiffened by J-shaped ribs. The basic principles of dynamic four-step phase shifting technique and multi-frequency unwrapping method in the fringe projection profilometry are introduced. These techniques were used to monitor the morphological changes of the composite panel under in-plane compression. At the same time, strain gauges were utilized to monitor strain history at each point on the surface of the panel. Optical measurement shows the full-field buckling deflection and buckling mode at different moments, and it produces richer data than strain gauges. The experimental results show that the local buckling increases with the loading until the ribs are unstable, which is verified by the finite element calculations.